INFLUENCIA DEL FACTOR CULTURAL EN EL USO DE MÉTODOS ANTICONCEPTIVOS EN MUJERES EN EDAD FÉRTIL ATENDIDAS EN PLANIFICACIÓN FAMILIAR EN EL HOSPITAL SANTA MARÍA DEL SOCORRO, 2019 - Romano Diaz, Cynthia Evelyn (2020)
Among the results we have found that there is no significant influence of the cultural factor in the use of contraceptive methods in women of childbearing age treated in family planning at the Santa María del Socorro hospital, that the cultural factor is predominant and that cultural factors such as Taboo, attitude of the couple and religion are present in a minimum percentage in the use of contraceptive methods in women of childbearing age attended in family planning at the Hospital Santa María del Socorro, 2019. In relation to the sociodemographic characteristics of the sample under study, He found that the age of 20 to 35 years, the condition of living together and the degree of non-university education predominate in women who attend the family planning service of the establishment. Conclusion: the cultural factor does not influence the use of contraceptive method in women of childbearing age assisted in family planning. Keywords: cultural factor, contraceptive methods, women of childbearing age